Breadwinner or Caregiver? How Household Role Affects Labor Choices in Mexico - Cunningham, Wendy V. (World Bank, Washington, DC, 2014)
Recent volatility in the Mexican economy, has required households to alter patterns of participation in the labor force, voluntarily or not. The author uses panel data to examine patterns of labor force entry among adult men, and women with different household responsibilities, asking whether gender is a primary determinant, shaping these patterns. She finds that labor supply patterns are driven more by household role, than by gender. Heads of households, regardless of sex, behave similarly. Women who have neither spouses, nor children behave more like men, than like married women. They are also more likely than any other group to have inflexible, higher-paying jobs in the formal sector - which raises the question: Do employers discriminate, based on gender, or on household structure? She also detects a strong added-worker effect among secondary workers, a result not detected in the labor markets of developed countries that have social insurance programs. Finally she finds that wives' choice of sector during downturns, is subject to the households' earning needs, that husbands use informal wage, or contract employment as an employer of last resort, only in response to negative income shocks to the household, and that single mothers do not select the informal sector over the formal sector in response to either expected, or realized negative income shocks. The policy implications? Interventions that target women aren't necessarily appropriate, because women are heterogeneous. And programs that aid household heads - male or female - should be directed toward employment that will last beyond the economic shock.